Monetary Transmission via the Central Bank Balance Sheet - Stefan Behrendt (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2013)
This paper estimates the effects of unconventional monetary policies on consumer as well as asset price inflation, economic activity and bank lending at the hand of a VAR analysis, covering episodes of balance sheet policies of 9 countries over the last 20 years. While recent episodes of unconventional monetary policies have been extensively analysed, this paper reduces deficiencies about long-run implications following central bank balance sheet policies in Scandinavian countries, Australia in the 1990s and Japan in the early 2000s. Results of this study are that balance sheet policies, in response to a collapse of asset price bubbles, can ensure a short run stabilisation of economic activity but are not able to lift the economy out of the ensuing deflationary slump alone. Additionally, they do not pose severe problems associated with inflation, as laid out in several theories such as the static monetarist interpretation of the quantity theory of money, or towards newly created asset price bubbles.
urn:nbn:de:gbv:27-20131202-111212-8
Keywords: C32; E31; E44; E51; E52; E58; 330; unconventional monetary policy; zero lower bound; money multiplier; VAR